A Comprehensive Survey on Security Challenges and Techniques in Big Data - Vijayaganth, V.; Purusothaman, P.; Krishnamoorthi, M. (International Journal of Psychosocial Rehabilitation, 2020)
Data plays a major role in most of the business today. Due to smarter life style, data is generated at high volume, variety and velocity. This led to new problems in the current systems. Big data has evolved to address the problems in conventional system which cannot hold large volume of data. However, there exist problems associated to data security and privacy in the big data system. In the literature there are several solutions to address these problems. This paper presents an overview on the basic notion of big data and data analytics, some techniques and also presents some of security problems associated to big data.